Impact of Regulatory and Technological Environment Factors on Electronic Commerce Use and Performance: A Field Study in Retail Sector in Saudi Arabia - Al Waki, Mohammed (Jordan Journal of Business Administration, 2019)
This study aimed to investigate the role of regulatory and technological environment factors in influencing the scope of e-commerce use and performance of retail companies in Saudi Arabia. A number of factors have been identified that affect the scope of e-commerce use in the retail sector in Saudi Arabia. The researcher surveyed 27 large retail stores that already adopted e-commerce. The structural equation modeling (SEM) method was used to analyze data. The results indicated that the scope of use of e-commerce has a positive impact on business performance in terms of improving internal processes and competitive position, providing customer services, enhancing the overall business performance and increasing the customer base. The scope of use of electronic commerce is positively influenced by the perceived benefits of electronic commerce and is negatively affected by the barriers to the use of electronic commerce. The results focused on key areas requiring serious e-commerce actions in Saudi Arabia's retail sector to boost growth in the sector.